Determinants of choice of economic sector in the non-farm economy in Ghana. (2016) - Owoo, Nkechi S.
This paper examines the economic sector choice of individuals in the non-farm economy, using the 2012 Ghana Living Standards Survey (GLSS). The multinomial logit regression results indicate that factors that influence individuals' decisions to participate in the non-farm economy differ for the different sectors - manufacturing, wholesale/retail and services. This research emphasises the heterogeneous nature of choice and entry into various sectors of the non-farm economy in Ghana. From a policy perspective, the findings may signal the various policy measures that policy-makers may adopt in order to increase participation into a targeted sector, and promote long-term growth and development of the country.